Location choices of Swedish independent schools: How does allowing for private provision affect the geography of the education market? - Karin Edmark (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2018)
This paper studies the location decisions of Swedish start-up independent schools. It makes use of the great expansion of independent schools following a reform implemented in 1992 to test what local market characteristics are correlated with independent school entry. The results suggest that independent schools are more likely to choose locations with a higher share of students with high-educated parents; a higher student population density; and a lower share of students with Swedish-born parents. There is also some evidence that independent schools are less likely to locate in municipalities with a left-wing political majority. These results are robust to various alternative and flexible definitions of local school markets, which were employed in order to alleviate the Modifiable Areal Unit Problem. For some of the included variables, the definition of the local market however had a large impact on the results, suggesting that the issue of how to define regions in spatial analyses can be important.
Keywords: H44; I28; L19; R32; 330; Private provision; mixed markets; education sector; Modifiable Areal Unit Problem